The Palgrave Handbook of African Women's Studies 2020
DOI: 10.1007/978-3-319-77030-7_29-1
|View full text |Cite
|
Sign up to set email alerts
|

Women in African Marriages

Abstract: This chapter highlights the voice, visibility, and value of women in African marriages under the themes of bride price, the communal nature of weddings, and response to marital infidelity. Women feature in marriages in Africa in unique yet ambivalent ways, both in how marriages are contracted and in the expectations of marital relationships. They struggle to be heard, seen, and respected, which undermines their voice, visibility, and value. This tripod comprises of about five articles in the 2003 Maputo Protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Given that a considerable proportion of our cohort consists of married women who also work as housewives, they are likely to continue their domestic work despite their headaches because of the demands of homekeeping in our setting of relative patriarchal dominance. 22 Further buttressing our hypothesis is the reduction of the number of days of reduced household efficiency by 50%. Our findings also suggest that many patients with migraine might feel that when having a headache, they would rather have reduced efficiency at work rather than skip work, as noted by other authors.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Given that a considerable proportion of our cohort consists of married women who also work as housewives, they are likely to continue their domestic work despite their headaches because of the demands of homekeeping in our setting of relative patriarchal dominance. 22 Further buttressing our hypothesis is the reduction of the number of days of reduced household efficiency by 50%. Our findings also suggest that many patients with migraine might feel that when having a headache, they would rather have reduced efficiency at work rather than skip work, as noted by other authors.…”
Section: Discussionmentioning
confidence: 66%
“…Another item, “the number of days of missed household work” had a low median score on the MIDAS‐K. Given that a considerable proportion of our cohort consists of married women who also work as housewives, they are likely to continue their domestic work despite their headaches because of the demands of homekeeping in our setting of relative patriarchal dominance 22 . Further buttressing our hypothesis is the reduction of the number of days of reduced household efficiency by 50%.…”
Section: Discussionmentioning
confidence: 84%
“…This discriminatory practice interacts closely with poverty consequently, hinders the opportunity of obtaining good jobs and substantial income. It important note that in Nigeria like some African countries, the traditional society allows inequitable gender norms which prioritize feminine roles as wives, mothers, and household caretakers (Olaore and Agwu, 2020). Alternatively, the education of the girl-child is restrained to informal domestic education at home, on hygiene, cooking, laundry and general home management.…”
Section: Discussionmentioning
confidence: 99%
“…This discriminatory practice interacts closely with poverty and consequently, hinders the opportunity of obtaining good jobs and substantial income. It is important to note that in Nigeria like some African countries, the traditional society allows inequitable gender norms which prioritize feminine roles as wives, mothers, and household caretakers [ 22 ]. Alternatively, the education of the girl-child is restrained to informal domestic education at home, on hygiene, cooking, laundry and general home management.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, most rural indigenes owing to proximity, migrate to the town for healthcare services. In addition, studies have shown that the locality is one of the disease holo-endemic Nigerian communities with great economic burden on healthcare financing [ 22 , 35 ]. The estimated population of Nsukka is 309,448 comprising 149,418 males and 160,030 females [ 8 ].…”
Section: Methodsmentioning
confidence: 99%